CHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF DONUTS FROM SEVERAL TYPES OF SWEET POTATO FLOUR - Sidabalok, Inawaty; Salihat, Rera Aga; Farid, Muhammad; Fitria, Eddwina Aidila (JURNAL KATALISATOR, 2024)
Donuts are a snack made from wheat flour and are popular among various groups. However, wheat flour contains gluten, which can cause the immune system of a person with celiac disease to react to gluten and attack the small intestine lining. Therefore, wheat flour needs to be substituted with alternative ingredients, one of which is sweet potato flour. This research aims to determine the effect of different types of sweet potato flour in making donuts on their chemical and organoleptic characteristics. The research design used was a Completely Randomized Design (CRD) with five treatments and three replications. Observation data were analyzed using ANOVA and Duncan's New Multiple Range Test (DNMRT) at α = 1%. The treatment in this study was the addition of variations of sweet potato flour (A = 50% white sweet potato, B = 50% purple sweet potato, C = 50% yellow sweet potato, D = 50% orange sweet potato, E = 50% cilembu sweet potato). Further test results showed that the addition of various variations of sweet potato flour had very significantly different effects on moisture, ash, fat, protein, carbohydrate content, and antioxidant activity. Based on organoleptic tests, the best treatment was treatment E (cilembu sweet potato flour) with an average value of 5.93 (very like), where the resulting donuts had the following chemical characteristics: moisture content (24.18%), ash content (2.10%), fat content (10.87%), protein content (14.96%), carbohydrate content (56.74%) and antioxidant activity (64.75%). Donuts with cilembu sweet potatoes have the most fragrant aroma, golden brown color, slightly sweet taste, and soft texture.